The microstructure, optical and gas sensing properties of bilayer TiO2/ZnO systems in terms of annealing temperature - Kheiri, Fariba; Soleimanian, Vishtasb; Ghasemi, Mohsen; Mokhtari, Ali (Materials science in semiconductor processing, 2021)
Similar to the single layers, the electrical and optical parameters of bilayer systems strongly depend on the crystallite properties (size, shape and distribution function) and the lattice defects of each layer. Moreover, the interactions and processes between the particles at the interface of two layers can affect directly the physical properties of bilayer films. In order to study the above subject, in this study two famous metal oxide semiconductors i.e. zinc oxide and titanium oxide are selected. The bilayer films are annealed at temperature interval between 400 and 600°C. The phase fractions, microstructure parameters and surface morphology of the films are studied as a function of annealing temperature, using the X-ray diffraction patterns and scanning electron microscope images which confirm the presence of two various ZnO components with different crystallite size and lattice strain. The effective optical band gap in addition to the refractive index of films are estimated as a function of the annealing temperature, crystallite size and density of defects. The gas sensing properties of films in the presence of ethanol gas are also studied as a function of time interval, gas concentration and operating temperature. Finally, the effects of X-ray diffraction analysis and scanning electron microscope results are investigated on the gas sensitivity of our bilayer films.